Factors Affecting the Aldosterone/Renin Ratio - Stowasser, M.; Ahmed, A. H.; Pimenta, E.; Taylor, P. J.; Gordon, R. D. (Hormone and Metabolic Research, 2012)
Although the aldosterone/renin ratio (ARR) is the most reliable screening test for primary aldosteronism, false positives and negatives occur. Dietary salt restriction, concomitant malignant or renovascular hypertension, pregnancy and treatment with diuretics (including spironolactone), dihydropyridine calcium blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor antagonists can produce false negatives by stimulating renin. We recently reported selective serotonin reuptake inhibitors lower the ratio. Because potassium regulates aldosterone, uncorrected hypokalemia can lead to false negatives. Beta-blockers, alpha-methyldopa, clonidine, and nonsteroidal anti-inflammatory drugs suppress renin, raising the ARR with potential for false positives. False positives may occur in patients with renal dysfunction or advancing age. We recently showed that (1) females have higher ratios than males, and (2) false positive ratios can occur during the luteal menstrual phase and while taking an oral ethynylestradiol/drospirenone (but not implanted subdermal etonogestrel) contraceptive, but only if calculated using direct renin concentration and not plasma renin activity. Where feasible, diuretics should be ceased at least 6 weeks and other interfering medications at least 2 before ARR measurement, substituting noninterfering agents (e. g., verapamil slow-release±hydralazine and prazosin or doxazosin) were required. Hypokalemia should be corrected and a liberal salt diet encouraged. Collecting blood midmorning from seated patients following 2–4 h upright posture improves sensitivity. The ARR is a screening test only and should be repeated once or more before deciding whether to proceed to confirmatory suppression testing. Liquid chromatography-tandem mass spectrometry aldosterone assays represent a major advance towards addressing inaccuracies inherent in other available methods.
Keywords: primary aldosteronism; screening; aldosterone; renin; aldosterone/renin ratio; assay